Unraveling the role of CH3S intermediates for efficient methane and hydrogen sulfide reforming over Mo/Al2O3 catalysts - Wu, Jundao; Huang, Zeai; He, Zhen; Zairov, Rustem; He, Xiaoting; Huang, Yue; Fu, Mengyao; Yuan, Chengdong; Sinyashin, Oleg G.; Zhou, Ying (Journal of catalysis, 2025)
Direct evidence for the reaction pathway of methane and hydrogen sulfide reforming (H2SMR) was obtained by in situ diffuse reflectance infrared Fourier-transform spectroscopy (DRIFTS). [Display omitted] •CH3S* as key intermediate in H2SMR converts CH4/H2S to H2/CS2.•H2SMR’s synergistic effects set it apart from CH4/H2S cracking.•Catalyst stability prolonged by preventing sulfur/carbon deposition. The catalytic methane(CH4) and hydrogen sulfide(H2S) reforming (H2SMR) represents a promising approach for producing high-value sulfur-carbon compounds and hydrogen without generating the greenhouse gas of CO2. Despite its significant potential, the mechanistic understanding of interactions between CH4 and H2S remains contentious, posing substantial challenges for catalyst development. In this study, we employed a Mo/Al2O3 catalyst to elucidate synergistic conversion pathways between CH4 and H2S during H2SMR. At 1173 K with a reaction duration of 0.5 h, conversion rates of CH4 and H2S reached 63.7 % and 59.2 %, respectively, accompanied by H2 and CS2 production rates of 688.8 μmol g−1 min−1 and 444.3 μmol g−1 min−1, respectively. Notably, the catalyst exhibited stable performance over 5 h without significant deactivation, in contrast to pure methane cracking reactions where CH4 conversion rapidly declined from 43.6 % to 14.3 %. Through in-situ diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS) combined with alternating CH4/H2S exposure experiments, we successfully tracked the synergistic conversion pathway on the Mo/Al2O3 catalyst. These investigations revealed that the formation of CH3S intermediates serves as a critical step facilitating CS2 generation. This mechanistic insight not only advances fundamental understanding of H2SMR reaction pathways but also provides a rational foundation for designing optimized catalysts with enhanced stability and extended operational lifetimes. The identification of this intermediate-driven mechanism addresses previous controversies regarding CH4-H2S interactions and offers strategic guidance for developing efficient sulfur-resistant catalytic systems.